PENGARUH TENAGA KERJA DAN PENGELUARAN PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN ENREKANG - Warda, Warda; Astina, Sri Wahyuni (Perpustakaan dan Penerbitan Unismuh Makassar, 2015)
This study examines labor, government expenditure and economic growth in Enrekang Regency. The approach used in this study is a quantitative descriptive approach. The type of research used is a correlational research design that is to determine the relationship between independent variables and dependent variables. Population in this study is the entire community which includes a workforce of 9,588 people and a sample of 99 inhabitants. Methods of data collection by questionnaire research, field and literature. Methods of data analysis using multiple regression analysis. The results showed that labor is not significant to economic growth and government expenditure significant to economic growth in Enrekang Regency.